AGREEMENT AND VALIDITY BETWEEN BODY FAT ESTIMATED BY SKINFOLD MEASUREMENT AND AIR DISPLACEMENT PLETHYSMOGRAPHY IN ADOLESCENTS CONCORDÂNCIA E VALIDADE ENTRE A GORDURA CORPORAL ESTIMADA POR MEDIDAS DE DOBRAS CUTÂNEAS E PLETISMOGRAFIA POR DESLOCAMENTO DE AR EM ADOLESCENTES - Bim M.A.* (2023)
© 2023 Universidade Estadual de Maringa. All rights reserved.Objective: Assess the agreement and validity between relative body fat percentages estimated using anthropometric measurements and air displacement plethysmography (ADP). Methods: A cross-sectional study was conducted on 118 adolescents (60 females) aged 10 to 14 years (x=̄12.19, sd=1.18). Adolescents were classified as eutrophic or with overweight according to body mass index (body weight/height2) (x̄=20,12, sd=3,56). Measurements of skinfold thickness (triceps and medial calf) were collected and used to estimate relative body fat by the Slaughter equation. ADP was used as a reference method for the estimation of relative body fat. Agreement between body fat measurement methods (anthropometry × ADP) was analyzed by the Bland–Altman method. The mean error (ME) was calculated by subtracting the body fat percentage estimated by the Slaughter equation from the body fat percentage estimated by ADP. Validity was tested with the concordance correlation coefficient (CCC). Results: There was no agreement between the methods, regardless of sex and weight status. For boys with overweight (ME = 4.52; p = 0.007), eutrophic girls (ME = 6.37; p < 0.001), and girls with overweight (ME = 5.55; p < 0.001), the Slaughter equation resulted in overestimation of body fat compared with ADP. Skinfold equations did not demonstrate validity when compared with ADP. Conclusion: Slaughter's skinfold equations did not demonstrate agreement and validity compared with ADP in either sex or weight status. Skinfold equations should be used with caution and, whenever possible, in combination with other body composition indicators.